2016
DOI: 10.1242/dev.135848
|View full text |Cite
|
Sign up to set email alerts
|

Identification of STAM1 as a novel effector of ventral projection of spinal motor neurons

Abstract: During spinal cord development, motor neuron (MN) axons exit the spinal cord ventrally, although the molecular basis for this process remains poorly understood. STAM1 and HRS form a complex involved with endosomal targeting of cargo proteins, including the chemokine receptor CXCR4. Interestingly, the absence of CXCR4 signaling in spinal MNs is known to result in improper extension of the axons into the dorsal side of the spinal cord. Here, we report that the MN-specific ISL1-LHX3 complex directly transactivate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
(114 reference statements)
0
4
0
Order By: Relevance
“…Over 50% of the 259 host cell protein interactors of SARS-CoV-2 3CL pro were associated with the cytoskeleton. Many of these are 3CL pro substrates with roles in regulating the formation of cell protrusions, including filipodia and dendrites, e.g., LASP1 39 , NUMA1 70 , drebrin 49 , and STAM 67 . The Arp2/3 complex is central to the formation of cellular protrusions since it nucleates branched actin assembly that provides the pushing force for plasma membrane deformation 71 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 50% of the 259 host cell protein interactors of SARS-CoV-2 3CL pro were associated with the cytoskeleton. Many of these are 3CL pro substrates with roles in regulating the formation of cell protrusions, including filipodia and dendrites, e.g., LASP1 39 , NUMA1 70 , drebrin 49 , and STAM 67 . The Arp2/3 complex is central to the formation of cellular protrusions since it nucleates branched actin assembly that provides the pushing force for plasma membrane deformation 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of signal transducing adapter molecule 1 (STAM) results in increased length of cell projections 67 , suggesting that STAM is inhibitory. STAM is a component of the endosomal sorting complexes required for transport (ESCRT)-0 complex that mediates membrane remodelling, vesicular transport and autophagy, and is hijacked by enveloped viruses to mediate budding 68 .…”
Section: Sars-cov-2 Infection Induces Translocation Of Centrosomal Pr...mentioning
confidence: 99%
“…ChIP was performed in mouse embryonic spinal cords as described previously (Nam and Lee, 2016; Cho et al, 2014; Lee et al, 2013). The spinal cords were microdissected from E12.5 mouse embryos and cells were dissociated and subjected to ChIP assays.…”
Section: Methodsmentioning
confidence: 99%
“…Genome-wide analyses of the Isl1-Lhx3 complex binding sites from chromatin immunoprecipitation-sequencing (ChIP-seq) datasets (Lee et al, 2013; Mazzoni et al, 2013) combined with MN transcriptome analyses (Lee et al, 2012; Mazzoni et al, 2013) identified many novel signaling pathways and regulators that are directly regulated by the Isl1-Lhx3 complex. Studies of individual target genes of the Isl1-Lhx3 complex in MN specification uncovered critical effector genes in MN specification such as genes involved in cholinergic neuronal identity determination (Cho et al, 2014), miR-218 as a downstream effector of Isl1-Lhx3 complex (Thiebes et al, 2015) and STAM1 as an endosomal sorting machinery necessary for ventral motor axon projection (Nam and Lee, 2016).…”
Section: Introductionmentioning
confidence: 99%